FEM Modal Analysis of Blades Number Effect in UAV Propellers - Ruseno, Neno (BRIN Publishing, 2024)
The propeller is one of the most important components in an Unmanned Aerial Vehicle (UAV) because it produces the thrust force. However, its structural strength is affected by the vibration phenomenon. The modal analysis can be used to study the dynamic behavior of mechanical structures under dynamic vibration. This study aims to analyze the vibration characteristics of UAV propellers in terms of propeller blade numbers using modal analysis. The propeller configurations used are two, three, and four blades. The Finite Element Method (FEM) is used to calculate the eigen frequencies of the system. The ANSYS Workbench is selected as the FEM software to simulate the study. The result shows that the propeller with 3 blades has the highest eigen frequency compared to the propeller with 2 and 4 blades which could make it preferable for UAV operations